Identification of Pivotal ceRNA Networks Associated with Stanford-A Aortic Dissection via Integrated Bioinformatics Analysis - Hu Y; Liu Z; Qin Y; Wu N; Yang T; Cheng X; Wang C; Wang X (International Journal of General Medicine)
Yuyuan Hu,1,* Zhenhao Liu,2,* Yan Qin,3,* Nan Wu,4 Tao Yang,2 Xinmeng Cheng,5 Chunyan Wang,6 Xuening Wang2 1Department of Cardiac Surgery, the First Affiliated Hospital of Shandong Second Medical University, Weifang, 261000, People’s Republic of China; 2Third Hospital of Shanxi Medical University, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences Tongji Shanxi Hospital, Taiyuan, 030032, People’s Republic of China; 3Department of Science and Technology Education, Shanxi Center for Clinical Laboratory, Taiyuan, 030012, People’s Republic of China; 4Department of Cardiac Surgery, Shanxi Provincial People’s Hospital, Fifth Hospital of Shanxi Medical University, Taiyuan, 030012, People’s Republic of China; 5Department of Cardiovascular Surgery, the Affiliated Cardiovascular Hospital of Shanxi Medical University and Shanxi Cardiovascular Hospital (Institute), Taiyuan, Shanxi, 030000, People’s Republic of China; 6Department of Clinical Laboratory, Shanxi Province Cancer Hospital, Shanxi Hospital Affiliated to Cancer Hospital, Chinese Academy of Medical Sciences, Cancer Hospital Affiliated to Shanxi Medical University, Taiyuan, 030013, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuening Wang, Department of Cardiovascular Surgery, Third Hospital of Shanxi Medical University, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, Tongji Shanxi Hospital, 99 Longcheng Road, Taiyuan, 030032, People’s Republic of China, Tel +86 15035118416, Email wangxuening2004@126.com Chunyan Wang, Shanxi Province Cancer Hospital/ Shanxi Hospital Affiliated to Cancer Hospital, Chinese Academy of Medical Sciences/Cancer Hospital Affiliated to Shanxi Medical University, No. 3 Zhigongxin Street, Xinghualing, Taiyuan, Shanxi, People’s Republic of China, +86 15110313926, Email chunyanwang2007@163.comObjective: Stanford-A Aortic dissection (TAAD) is a rare and fatal disease, genetic factors remains poorly known. Study has confirmed that lncRNA play an important role in various physiological and pathological processes. This study attempts to elucidate the underlying molecular mechanisms of TAAD through lncRNA-associated competitive endogenous RNA (ceRNA) networks.Methods: In this study, aortic vascular of 5 TAAD and 5 control (ischemic heart disease) were subjected to lncRNA and mRNA microarray analysis, and differentially expressed mRNAs (DEGs) and differentially expressed lncRNAs (DELs) were identified. The differentially expressed miRNAs (DEmiR) were screened by GSE98770 dataset. The ceRNA network (lncRNA-miRNA-mRNA) was constructed by bioinformatics analysis. The accuracy of hub genes as biomarkers for predicting TAAD was evaluated by receiver operating characteristic (ROC) curve. Finally, the biomarkers were verified by assessing their mRNA levels using real-time quantitative PCR (RT-qPCR).Results: This study revealed 161 DELs, 87 DEmiRs and 103 DEGs between TAAD and control. We constructed ceRNA networks based on the screened 1 lncRNA, 4 miRNAs and 7 mRNAs. We identified three lncRNA-miRNA-mRNA regulatory axes, namely the VCAN axis (LINC01355 - hsa-miR-186-5p / hsa-miR-30a-5p /hsa-miR-30c-5p - VCAN), LOX axis (LINC01355-hsa-miR-145-5p/hsa-miR-186-5p/ hsa-miR-30a-5p / hsa-miR-30c-5p - LOX), and CTSS axis (LINC01355 - hsa-miR-186-5p - CTSS) based on gene ontology, pathway enrichment and protein-protein interaction (PPI) network, which may play an important role in TAAD. The clinical performance of VCAN, CTSS, and LOX in TAAD diagnosis was evaluated, and the AUCs of VCAN, CTSS, and LOX were 0.920 (p< 0.001), 0.880 (p=0.002) and 0.840 (p=0.011), respectively. Furthermore, mRNA expression of VCAN in human aortic tissue significantly overexpressed in the TAAD patients (p< 0.001).Conclusion: This study identifies three ceRNA interaction axes, especially VCAN associated with TAAD pathogenesis, providing fundamentals of bioinformatics for understanding the molecular mechanisms of TAAD pathogenesis and developing potential therapeutic strategies for TAAD.Keywords: Stanford-A aortic dissection, lncRNA, ceRNA network, VCAN, bioinformatics analysis